Concept Analysis of Spirituality in Nursing - N Razaghi; F Rafii; S Parvizy; AS Sadat Hosseini (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Spirituality is a global phenomenon and everyone experience it. Nurses need to have a common understanding of spirituality before they begin to care for patients. However, there is yet ambiguity and disagreement on the definition and attributes of this concept. The present study was carried out to clarify the concept and reduce the semantic ambiguities in its definition to achieve a uniform, clear and understandable definition of spirituality in nursing. Material & Methods: Walker and Avant's eight-step model was used as the method. After extensive review of all published articles from 2000 to 2015, 42 articles were included into the analysis. By following the steps of the model, definitions, properties, applications, antecedents, consequences and empirical referents of the concept of spirituality were derived. Results: According to the analysis, spirituality as a metaphysical or transcendental phenomenon, includes properties of personal, subjective, and inner experience and the power of coordinating other aspects of existence, search for meaning and purpose of life and significant relations (personal, interpersonal and transpersonal (God or a higher power). The consequences of the concept of spirituality include health or relief of suffering, coping, comfort, hope and finally, transcendence. The definition of spirituality will be influenced by the perspective of human-centered philosophy (and secular), or God-centered philosophy. A conceptual model was proposed based on the findings. Conclusion: The concept of spirituality has different meanings depending on the cultural and philosophical background. In fact, it is a totally context dependent concept. Further research is suggested in this area, especially in the Islamic - Iranian context.